Atmospheric, Geomorphological, and Compositional Analysis of Martian Asimov and Hale Craters: Implications for Recurring Slope Lineae - Howari, Fares M.; Sharma, Manish; Xavier, Cijo M.; Nazzal, Yousef; Alaydaroos, Fatima (Frontiers in Astronomy and Space Sciences, 2022)
Recurring Slope Lineae (RSL) are small, dark, seasonal albedo features lengthening down “warm” Martian steep slopes. Their origin has been attributed to both liquid and dry processes, hence representing one of the major open science questions on present day Mars. In the present study, we report a catalog of previous literature and newly added RSL sites making a total of 940 sites globally on Mars along with the detailed geological and compositional investigation of Hale and Asimov craters with their RSL features. We also estimate temperature and atmospheric water abundances in the study area, which are one of the main factors to explain the origin and formation of RSL. The study found that Asimov crater’s local temperatures are high enough to allow either the melting of brines or deliquescence of calcium perchlorate and other salts during the HiRISE observation period and found the water vapor column to be nearly five times higher than those measured “before RSL appearance”. This supports the theory of deliquescence as one of the mechanisms for the regolith-atmosphere interaction and RSL formation in the studied crater, which suggests that minerals absorb moisture from the environment until the minerals dissolve in the absorbed water and yield a solution. We also used Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) derived browse products for a compositional study associated with RSL features hosting craters and surface characteristics of Mars.